Хеуристика и пристрасност во одлучувањето кај претприемачите: влијанието на индивидуалните и организациските фактори врз преголемата увереност - Илиева, Викторија (Економски факултет, УКИМ, Скопје, 2018)
This dissertation is focused on the overconfidence bias as one of the most typical biases in entrepreneurial decision making. The empirical research includes entrepreneurs from Macedonia and Austria and it deals with their overconfidence in general knowledge. The key question which is addressed in the research is whether entrepreneurs manifest overconfidence and if there is a difference between entrepreneurs from the two countries. Furthermore, when measuring the bias score the hard-easy effect is considered. The research within this dissertation is most importantly drawing on individual, organizational and environmental factors associated with founders’ miscalibration. The research hypotheses which are related to the determinants of overconfidence are checked by using bivariate and multivariate analyses. Results show that entrepreneurs from both countries are indeed overconfident regarding their knowledge, as it was expected following previous research conducted among entrepreneurs from the USA. However, there is a difference in overconfidence level between the two samples, how the hard-easy effect reflects on the bias score, as well as the predictors that show to be significant in each sample. These differences are discussed, and bearing in mind that no similar research has previously been done in a European country, it is relevant to compare the obtained results to those pertaining to entrepreneurs from the USA. Besides the theoretical implications from this research which can be ascribed to the specific form of overconfidence being addressed, the measure applied and the two samples of real entrepreneurs from two different countries, there are also practical implications for current and potential entrepreneurs.
Heuristics and biases in entrepreneurial decision making: the influence of individual and organizational factors on overconfidence
Докторска дисертација одбранета во 2018 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубомир Дракулевски.
Keywords: entrepreneurs, decision making, cognitive biases, overconfidence, Macedonia, Austria